Evaluation of Complications Associated with Periacetabular Osteotomy in Young Adult Patients - David G. Pliev; Vitalii S. Cherkasov; Anton N. Kovalenko (Travmatologiâ i Ortopediâ Rossii)
Background. Periacetabular osteotomy (PAO) is an effective method to prevent or delay the need for hip replacement surgery in young adults, though it carries a certain risk of complications. It is essential to study the factors influencing the complications rate in order to optimize surgical techniques and improve the outcomes.